Strength properties of latex based rubberized concrete with 15 kg/m3 steel fiber - Eng, Emily Le Yi (2023)
Nowadays, the disposal of waste tires has led to serious environmental issues due to the rubber material being non-biodegradable. Hence, the way to reduce the number of waste tires is by converting waste tires into valuable and useful products and materials. Crumb rubber is one of the materials that can be added to concrete to form rubberized concrete. Rubberized concrete has better impact resistance, toughness and ductility but possesses lower strength than regular concrete. The reduction in mechanical strength can be attributed to the weak interfacial transition zones between the crumb rubber and hardened cement paste. The use of steel fiber and SBR latex has the ability to make up for the strength loss caused by the incorporation of crumb rubber. In addition, it should be noted that concrete exhibits a deficiency in its ability to withstand tensile forces, thereby requiring the incorporation of steel fiber in order to enhance its tensile capacity. Thus, this study examines the impact of incorporating steel fiber into latex based rubberized concrete (LRC) on compressive, flexural and splitting tensile strengths, as well as impact resistance. The optimum mix proportion of trial mix for both LRC and Latex based rubberized concrete with 15 kg/m3 steel fiber (LRC-15 % SF) that had achieved at least 55 MPa of 28 days compressive strength was selected to test for the compressive, flexural and splitting tensile strengths, as well as impact resistance. Experimental results showed that steel fiber incorporation induced an enhancement in the strength properties of LRC. The experimental results indicate that the LRC-15 % SF with a W/C ratio of 0.28 exhibited superior performance compared to the control mixture with the same W/C ratio. Specifically, the LRC-15 % SF demonstrated a 3.18 % increase in compressive strength, a 10.70 % increase in splitting tensile strength, and a 17.94 % increase in flexural strength after 56 days of curing. Besides, the LRC-15 % SF showed higher impact resistance by 46.27 % and 14.71 % in the 400 mm and 200 mm span length impact test at 56 days, respectively. In short, the inclusion of steel fiber enhanced the performance of the concrete structure.